Integrating Flipped Classroom and Problem-Based Learning to Enhance Self-Efficacy and Problem-Solving in Higher Education - Miftahus Surur; Yesi Puspitasari; Siti Karunia Dewi (AL-ISHLAH: Jurnal Pendidikan, 2026)
The increasing demand for 21st-century competencies in higher education highlights the need for instructional approaches that enhance students’ self-efficacy, learning autonomy, and problem-solving skills. While Flipped Classroom (FC) and Problem-Based Learning (PBL) have been widely studied independently, their integrated effects remain underexplored, particularly in the Indonesian context.This study employed a quasi-experimental design with a nonequivalent control group involving 70 undergraduate students. The experimental group (n = 35) received an integrated FC-PBL intervention over one semester, while the control group (n = 35) experienced conventional instruction. Data were collected using validated instruments measuring academic self-efficacy, self-directed learning, and problem-solving ability. Statistical analyses included independent samples t-tests and MANOVA.The findings revealed that the experimental group significantly outperformed the control group in academic self-efficacy (t(64) = -3.473, p = .001), self-directed learning (t(64) = -5.991, p .001), and problem-solving ability (t(64) = -2.475, p = .016). Multivariate analysis confirmed a significant overall effect of the intervention (Hotelling’s Trace = 0.836, F(3, 62) = 17.274, p .001, partial η² = 0.455), indicating a large effect size.The integration of FC and PBL significantly enhances students’ affective, metacognitive, and cognitive outcomes. This study provides empirical support for FC-PBL as an effective pedagogical approach to foster essential competencies in higher education. Future research should employ randomized and multi-institutional designs to improve generalizability.